Public administration : the basics - Schiavo-Campo, Salvatore (New York, NY : Routledge, 2023)
"There is a distinction between public policy ("what is to be done") and public administration ("how it is to be done"). The outcomes of government policies depend in large part on how policies are executed and who is responsible for their execution. Public administration is the set of instruments -- the rules, incentives, organizations, information, systems and people -- to implement public policy. Public Administration: The Basics is a reader-friendly and up-to-date synthesis of the subject, complete with relatable examples, analogies, and real-world illustrations. The book, grounded on a sound conceptual basis, offers practical insight without jargon and, despite its short length, covers all major topics. The first three chapters describe the functions and organizational structure of government; the next three focus on the core issues of the management of public finances, government personnel, and public procurement; the final three chapters address government regulation, the provision of public services, and the interaction between government and the private sector. Public Administration: The Basics is an ideal first book for introductory public administration courses, as well as complementary reading for courses in political science, public economics and international affairs. The book also serves as an accessible reference for busy policymakers, civil servants and engaged citizens"--
Includes bibliographical references.
Keywords: Public administration -- United States; United States -- Politics and government